Conceptual Framework of Synergy Leadership Style and Organizational Culture on Human Resource Performance in Indonesia - Syafri, Muhammad; Wahdiniawati, Siti Annisa; Renggaala, Nuniek Yuniarti Ningsih; Nur Ayu; Ridhayantho, Muhamad (Westscience Press, 2025)
This study examines the influence of synergy leadership style and organizational culture on human resource performance in Indonesia. Using a quantitative research design, data were collected from 150 respondents across various organizations through a structured questionnaire measured on a five-point Likert scale. The data were analyzed using SPSS version 25, employing descriptive statistics, reliability and validity tests, correlation analysis, and multiple regression. The results reveal that both synergy leadership style and organizational culture significantly and positively affect human resource performance. Specifically, organizational culture emerged as the stronger predictor compared to leadership style, emphasizing its vital role in shaping employee behavior and performance outcomes. The study contributes to the literature by providing empirical evidence on the interaction between leadership and culture in the Indonesian context, highlighting their combined importance in enhancing employee productivity, innovation, and organizational sustainability. Practical implications suggest that leaders and policymakers should foster synergistic leadership practices alongside cultivating a strong organizational culture to achieve long-term performance excellence.